Efek Samping Aspirin - Tisa Angelia (Yayasan Pendidikan Medika Indonesia, 2021)
Aspirin is a salicylate derivative with the chemical name acetylsalicylic acid. The drug is used as an analgesic, antipyretic, anti-inflammatory and anticoagulant. Aspirin belongs to the class of non-steroidal anti-inflammatory drugs (NSAIDs). In addition to treating pain, fever, and inflammation, aspirin can be used to prevent strokes and heart attacks. Side effects of aspirin need to be considered given the high use of this drug. The purpose of this paper is to determine the side effects of aspirin. The method used is a literature review with the keywords aspirin, pharmacology, and treatment on Google Scholar and Pubmed. Searching the literature from both national and international journals then summarizes the discussion topics and compares the results presented in the articles. From a review of the existing literature, side effects of aspirin include bleeding, hypersensitivity reactions, and death.